Studying the Effects of Vacancies on the Melting Temperature of \(\text{AgCe}\) Alloy - Hai, Dang Thanh; Hung, Vu Van; Hong, Giang Thi (Communications in Physics, 2018)
In order to evaluate the effects of vacancies on the melting temperature of AgCe alloy, the statistical moment method was used to find out the analytical expressions to determine the Gibbs free energy in the AB substitution alloy and the expression to calculate the melting temperature of perfect and imperfect AB substitution Alloys. The melting temperature was calculated by the numerical calculation method on the perfect and imperfect AgCe alloy. The calculating results shown that the melting temperature of alloys increase with a increase in pressure. The melting temperatures of imperfect alloy of AgCe, Ag2Ce and Ag3Ce are always slightly lower than that of perfect alloys. Especially, the melting temperatures value of perfect and imperfect alloy were almost the same at high pressure. The melting temperature of alloys increase with an increase in amount of Ag containing in the alloys. The calculated results agreed well with the experimental results at P = 0.